Analysis Student Needs for the Development of Contextual-Based STEM Approach Learning Media in Online Learning: An Evidence from Universities in Jambi, Indonesia - Pathoni, Haerul; Ashar, Rayandra; -, Maison; Huda, Nizlel (Universitas Terbuka, 2021)
In 2020, higher education must implement online learning because of pandemic COVID 19. Learning with the science, technology, engineering, and mathematics(STEM) approach is rarely done in online learning.The first step in implementing the STEM approach on campus in online learning is to develop contextual learning media based on the STEM approach.This study analyzes students' needs for contextual learning media based on the STEM approach in Basic Physics courses in online learning. This research method is a descriptive study with research subjects are 141 second and third-year students of the Physics Education Program ofUniversitas Jambi and the State Islamic University of SulthanThahaSaefudin Jambi.The subject has completed basic physics courses. Data collection was carried out from preliminary observations and the use of a student needs analysis questionnaire.The results showed that students found it difficult to understand several topics in basic physics subjects.It is caused by a lack of instructional media, a lack of descriptions, a less detailed description of formulas, inadequate use of the STEM approach, and a lack of higher-order thinking skills for student practice.From the questionnaire results, it was also found that students needed learning media with a contextual-based STEM approach to help them understand the topics of Basic Physics courses in online learning.